Encapsulación de Gramicidina S en liposomas - Antezana, Pablo Edmundo (2023)
Gramicidin S (GraS) is an amphiphilic peptide that has emerged as an effective alternative antibiotic. However, its applicability is restricted for clinical uses due to its effect on eukaryotic cells and low aqueous solubility. In this work, a novel water-soluble peptide formulation with bactericidal activity is developed by the incorporation of Gramicidin S in the lipid bilayer of liposomes (L-GraS). As a result, GraS included in the lipid vesicles is stabilized in aqueous medium and showed antimicrobial activity against Staphylococcus aureus. In addition, L-GraS reveals enhanced biocompatibility with mammalian cells in comparison with the free peptide. Molecular dynamics simulations shed light on the collective behavior between GraS peptides and liposomes from a molecular approach. The molecular dynamic simulations are in agreement with experimental results and further confirm the effective incorporation of GraS in the liposomes, letting understand the best formulation procedure of the vesicles. Therefore, the L-GraS nanosystem presented here is an interesting alternative to conventional antibiotics, with less restrictions and promising features to improve current therapies. Practical Applications: Incorporation of GraS in liposomes is an interesting approach to increase the solubility of the peptide, thus expanding its therapeutic horizon as a promising alternative to combat bacterial colonization especially in wound infections.